Blood purification therapies in methotrexate-induced acute kidney injury: four case reports. Issue 1 (December 2017) - Fujikura, Emi; Akiu, Maho; Miyauchi, Kenichiro; Yoshida, Mai; Aoki, Satoshi; Yamamoto, Tae; Narumi, Kaori; Yanagisawa, Noriko; Nakamichi, Takashi; Miyazaki, Mariko; Sato, Hiroshi; Ito, Sadayoshi
Abstract Background Methotrexate (MTX), a folic acid antimetabolite, is administered at a high dose for the treatment of diseases such as leukemia and malignant lymphoma. Often, an effort is made to reduce the adverse effects of MTX by monitoring MTX concentration in the blood and administering a high dose of leucovorin. However, side effects of MTX are still reported. MTX is metabolized in the liver and eliminated via the kidneys; hence, blood purification therapy is useful for the reduction of MTX blood concentration in case of renal impairment. Case presentation We performed various types of blood purification therapies in four cases of MTX poisoning that accompanied renal impairment. Conclusions Based on our results, we concluded that hemodialysis or hemoperfusion with an activated carbon absorption column was useful for the elimination of MTX from the blood. It is important to choose an appropriate blood purification method understanding the characteristics of each blood purification method.